COMPARISON OF METHODS FOR EVALUATING UPPER LIMB STRENGTH BY HAND-HELD DYNAMOMETRY - Nepomuceno Júnior,Balbino Rivail Ventura (2021)
ABSTRACT Introduction The upper limbs are segments of the human body responsible for primary activities of daily life, and the muscles are essential structures for performing these activities. There have been few studies on intra- and inter-examiner reliability of the hand-held dynamometer (HHD) in healthy subjects, and none have been published that compare dynamometric evaluation methods in the main muscles in this segment. Objective Evaluate intra-examiner and inter-examiner assessment reliability of the hand-held dynamometry of upper limb muscles in healthy individuals, as well as comparing the assessment reliability between fixed and non-fixed methods. Methods Healthy subjects aged over 18 years were recruited for the study. The isometric contraction for ten muscle groups of the dominant upper limb was tested. For the fixed method, we used a system of suction cups, connected to the HHD by an inelastic belt. For the non-fixed method, the examiner supported the device by hand. The isometric contraction was sustained for three seconds. Each measurement was repeated three times, considering the highest value obtained. The reliability was calculated using the intraclass correlation coefficient (ICC). The dispersion between measurements was expressed by a Bland-Altman plot. Results The sample consisted of 25 volunteers, all right-handed. The intra-examiner ICC was 0.89-0.99 for the non-fixed method, and 0.43 to 0.85 for the fixed method. Inter-examiner reliability showed equivalent behavior. This study showed that evaluation of upper limb muscle strength using an isometric dynamometer has excellent intra-examiner and inter-examiner reliability. The supine position was chosen due to the need to propose a feasible protocol for clinical practice that could be replicated for the majority of publics and in different environments. The non-fixed method showed better reliability overall, demonstrating the feasibility of this tool without the need for adaptations, additional devices, or increased operating costs for this evaluation. Conclusion Comparison between the fixed and non-fixed HHD methods demonstrated superiority of the non-fixed method in terms of reliability. Level of evidence II; Investigation of a diagnostic exam - Development of diagnostic criteria with consecutive patients.